Divergent responses of plant lignin and microbial necromass to the contribution of soil organic carbon under organic and chemical fertilization - Chang, Xingping; Pei, Zhanjiang; Wang, Xiaofei; Wang, Hao; Mu, Jie; Ma, Yingjun; Zhang, Mingye; Zhang, Keqiang; Du, Lianzhu (Frontiers in Microbiology, 2025)
IntroductionLong-term fertilization strongly influences the formation, turnover and stabilization of soil organic carbon (SOC) in croplands. The underlying mechanism by which chemical fertilizer (CF) and cattle slurry (CS) application influence the dynamics of plant- and microbial-derived carbon (C) remains elusive.MethodsLignin phenols and amino sugars as well as microbial carbohydrate-active enzymes (CAZymes) were analyzed in a 10-year field experiment.ResultsCF and CS increased the content of SOC by 26.9% and 88.0% compared with the SOC content of an abandoned land, respectively. CS application increased lignin phenols content by 4.28 times compared with CF application owing to slower oxidative degradation and higher plant inputs. Microbial necromass C (MNC) contents increased by 34.7% in line with an increase in biomass, but its proportion to SOC did not change. In terms of microbial community, the application of CF and CS altered the distribution and structure of microbial community. The dominant bacterial phyla shifted from oligotrophic Actinomycetota to eutrophic Pseudomonadota with change in the application from CF to CS. CS application increased CAZyme genes associated with plant- and bacterial-derived fractions decomposition, suggesting higher degradation potential of plant and bacterial biomass by microorganisms. Availability of substrates and microbial community are important factors affecting SOC accumulation in different fertilization treatments.DiscussionCS application considerably promoted the accumulation of SOC, mainly via the promotion of plant-derived C. Alterations in microbial communities and CAZyme genes could affect microbial metabolism via “microbial carbon pump”, thereby facilitating SOC formation and accumulation.